2020
DOI: 10.1186/s13568-020-01072-w
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-143 targets MAPK3 to regulate the proliferation and bone metastasis of human breast cancer cells

Abstract: MicroRNAs (miRs) have shown tremendous potential to act as therapeutic targets for cancer treatment. In this context, the present study was designed to investigate the potential of miR-143 in the treatment of breast cancer. Results showed that miR-143 to be significantly (P < 0.05) downregulated in breast cancer tissues and cell lines. The miR-143 has inhibitory effect on CAMA-1cell growth which was manifested as significant (P < 0.05) decline in loss of viability of cancer cells. The loss of cell viability wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 23 publications
0
19
0
1
Order By: Relevance
“…Kundaktepe et al ( 44 ) reported that the expression level of miR-143 in peripheral blood mononuclear cells of breast cancer patients significantly decreased, which could be used as a breast cancer biomarker. In addition, human miR-143 can inhibit breast cancer cell proliferation and metastasis by regulating the gene expression of MAPK3 ( 45 ), MAPK7 ( 46 ), MYBL2 ( 47 ), CD44 ( 48 ), and ERBB1 ( 49 ) in cooperation with protein levels and phosphorylation status of AKT, Wnt/β-catenin, SAPK/JNK, and FAK of NF-κB signaling pathways and multiple oncoproteins in JAK/STAT signaling pathway ( 50 ). The expression level of miR-143 is related to the worst prognosis, which may be a potential predictor of neoadjuvant therapy response ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Kundaktepe et al ( 44 ) reported that the expression level of miR-143 in peripheral blood mononuclear cells of breast cancer patients significantly decreased, which could be used as a breast cancer biomarker. In addition, human miR-143 can inhibit breast cancer cell proliferation and metastasis by regulating the gene expression of MAPK3 ( 45 ), MAPK7 ( 46 ), MYBL2 ( 47 ), CD44 ( 48 ), and ERBB1 ( 49 ) in cooperation with protein levels and phosphorylation status of AKT, Wnt/β-catenin, SAPK/JNK, and FAK of NF-κB signaling pathways and multiple oncoproteins in JAK/STAT signaling pathway ( 50 ). The expression level of miR-143 is related to the worst prognosis, which may be a potential predictor of neoadjuvant therapy response ( 50 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mitogen-activated protein kinase 3 (MAPK3) belongs to the protein kinase superfamily and catalyzes the concomitant phosphorylation of a threonine and a tyrosine residue in the MAP kinase p38. It has been confirmed to be a potential therapeutic target for different kinds of human cancers, including CRC [43][44][45][46][47]. A previous study revealed that phosphorylated AMP-activated protein kinase (AMPK) expression in CRC was associated with superior prognosis among p-MAPK3 positive cases, indicating a possible interaction between the AMPK and MAPK pathways influencing tumor behavior [46].…”
Section: Discussionmentioning
confidence: 99%
“…e PI3K-Akt signaling pathway is altered in OSCC [51]. Invasion and migration can be suppressed in OSCC by inhibition of the PI3K-Akt signaling pathway [52]. Baicalein and wogonin induce apoptosis in many cancer cells by modulating the PI3K-Akt pathway [53,54].…”
Section: Discussionmentioning
confidence: 99%